2005
DOI: 10.4049/jimmunol.174.6.3220
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Binding Lectin-Deficient Mice Display Defective Apoptotic Cell Clearance but No Autoimmune Phenotype

Abstract: Mannose-binding lectin (MBL) is a circulating serum protein that is sequestered to sites of inflammation and infection. MBL is a member of the collectin family with structural similarities to the lung collectins and functional similarities to C1q. Both MBL and C1q activate complement; C1q activates the classical pathway and MBL the lectin pathway. Here we demonstrate that MBL binds apoptotic cells in vitro and confirm a role for MBL in clearance of apoptotic cells in vivo. Despite MBL null mice demonstrating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(128 citation statements)
references
References 36 publications
7
119
1
1
Order By: Relevance
“…Corroborating this notion is a recent study showing that late apoptotic (secondary necrotic) cells were just as effective as early apoptotic cells in terms of inhibiting ERK1/2 activity and stimulating JNK1/2 and p38, whereas necrotic cells had no detectable effect on c-Jun Nterminal kinase and p38 [113]. This view is supported by studies in which targeted deletion of CD14 or MBL in mice leads to in vivo persistence of apoptotic cells in the absence of inflammation and autoimmunity [114,115]. A reasonable conclusion is that the onset of secondary necrosis does not always carry inflammatory consequences.…”
Section: Interaction With Apoptotic Cells and Secondary Necrotic Cellsmentioning
confidence: 88%
See 1 more Smart Citation
“…Corroborating this notion is a recent study showing that late apoptotic (secondary necrotic) cells were just as effective as early apoptotic cells in terms of inhibiting ERK1/2 activity and stimulating JNK1/2 and p38, whereas necrotic cells had no detectable effect on c-Jun Nterminal kinase and p38 [113]. This view is supported by studies in which targeted deletion of CD14 or MBL in mice leads to in vivo persistence of apoptotic cells in the absence of inflammation and autoimmunity [114,115]. A reasonable conclusion is that the onset of secondary necrosis does not always carry inflammatory consequences.…”
Section: Interaction With Apoptotic Cells and Secondary Necrotic Cellsmentioning
confidence: 88%
“…However, these data contrast with the findings that macrophages from CD14-deficient Balb/c mice are less able to bind and internalize apoptotic cells both in vitro and in vivo, but exhibit no increase in anti-nuclear antibodies, and no obvious changes in the secretion of pro-or anti-inflammatory cytokines [114]. In the same way, MBLdeficient mice in a lupus-prone genetic background (129 × C57BL/6) also exhibit reduced apoptotic cell clearance (as measured by FACS analysis), but no increase in antinuclear antibodies or proteinurea, even at advanced age [115]. Interpretation of results obtained from different mouse strains used for modeling autoimmune diseases becomes difficult because the genetic background is very crucial for the development of the phenotype.…”
Section: Impairment Of Phagocytosis Of Dead Cells and Its Role In Thementioning
confidence: 91%
“…This seems unlikely, however, because we have also shown that late apoptotic cells mimic early apoptotic cells with respect to proinflammatory transcriptional activity (10) and inflammatory cytokine secretion (5). Moreover, even if delayed clearance contributes to the development of autoimmunity, it is not in and of itself sufficient to produce autoimmunity, because targeted deletion of CD14 or the mannose-binding lectin leads to the in vivo accumulation of apoptotic cells in the absence of autoimmunity (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The latter are then recognized by the complement receptors CR3 and/or CR4 expressed on phagocytes. MBL-deficient mice display a defect in apoptotic cell clearance, but show no signs of autoimmunity (Stuart et al 2005), while the C1q knockout presents with an SLE-like phenotype and impaired clearance of apoptotic cells (Botto et al 1998). Although a properdin-deficient patient developed a sclerotic form of SLE (Holme et al 1989), a definitive connection between properdin dysfunctions and SLE has not yet been established.…”
Section: Complement's Expanding Target Rangementioning
confidence: 99%